Improvement of the Antifungal Activity Against Botrytis Cinerea of Syringic Acid, a Phenolic Acid from Grape Pomace - Cotoras-Tadic, M; Guerrero-Nunez, J; Guerrero-Nunez, J; Campos-Deramond, A; Campos-Deramond, A; Zuniga-Navarro, G; Mendoza-Espinola, L; Mendoza-Espinola, L; Castro-Valenzuela, P; Castro-Valenzuela, P (Sociedad Chilena de Quimica, 2016)
The aim of this study was to improve the antifungal activity against Botrytis cinerea of syringic acid by using the enzyme laccase to synthesize a heterodimeric compound by a coupling reaction with aniline. The synthesized heterodimer is a quinone-imine like compound (2,6-dimethoxy-4-(phenylimino)benzenone), which was characterized by using 1H and 13C NMR, IR, and mass spectrometry. The antifungal activity of the heterodimeric compound against B. cinerea was determined in vitro and showed a higher antifungal effect than the substrates (syringic acid and aniline), inhibiting the mycelial growth with an IC50 value of 0.14mM and delayed 2 hours the conidial germination. Also, using the fluorochrome calcofluor white, cell wall damage was observed when B. cinerea was incubated with the compound. This is the first report on antifungal activity of this type of compound against B. cinerea. © 2016, Sociedad Chilena de Quimica. All rights reserved.